Investigating Hypoxic and Euxinic Area Changes Based on Various Datasets From the Baltic Sea - Krapf, Karina; Naumann, Michael; Dutheil, Cyril; Meier, H. E. Markus (Frontiers in Marine Science, 2022)
The Baltic Sea is a coastal sea with the world’s largest anthropogenically induced hypoxic bottom area. Although hypoxia has periodically occurred during the sea’s 8000-year history, the rapid rise in the population and intensified agriculture after World War II have led to nutrient input levels that have made hypoxia a permanent, widespread phenomenon. Efforts since the 1980s considerably reduced nutrient inputs in the Baltic Sea, but an improved ecological status in the deep basins of the Baltic Sea has yet to be achieved. In fact, hypoxic areas in those basins have reached record size and in some cases large euxinic areas have emerged. This study was based on a novel observational dataset comprising maps of hypoxic and euxinic areas of the Baltic Sea. The seasonal cycles of hypoxia and euxinia in the various sub-basins were investigated. The comparison of those maps with other observational and reanalysis datasets of hypoxia and euxinia revealed some discrepancies. Those discrepancies together with a pronounced interannual variability prevent the detection of robust trends in hypoxic and euxinic areas that would indicate an influence of decreasing nutrient inputs from the land and the atmosphere since the 1980s. A correlation analysis of physical drivers and hypoxic and euxinic areas suggests that climate change has already played an important role by enhancing oxygen depletion.